1992
DOI: 10.1523/jneurosci.12-04-01233.1992
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar cells specific for blue cones in the macaque retina

Abstract: A distinct subpopulation of bipolar cells in macaque monkey retina was labeled with antisera that recognize glycine-extended cholecystokinin precursors. The labeled bipolar cells were found throughout the retina and had dendrites contacting a subpopulation of cone pedicles and axons ramifying in the fifth stratum of the inner plexiform layer. Several lines of evidence indicate that the labeled bipolar cells are a single type despite some variations in their morphology. First, the density of perikarya and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
215
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(234 citation statements)
references
References 36 publications
19
215
0
Order By: Relevance
“…Cellular connections observed between (3-gal-expressing cone cells and some of the transgene-expressing bipolar cells suggest that at least some of the transgene-expressing bipolar cells may be specific for short-wave cone cells. Based on current knowledge of blue cone bipolar cells in the monkey retina, it is unlikely that the labeled bipolar cells are exclusively blue cone bipolar cells, which are reported to ramify in a single stratum of the inner plexiform layer (34). Thus the presence of two strata of ramification in the inner plexiform layer suggests that other classes of cone bipolar cells express the transgene as well.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular connections observed between (3-gal-expressing cone cells and some of the transgene-expressing bipolar cells suggest that at least some of the transgene-expressing bipolar cells may be specific for short-wave cone cells. Based on current knowledge of blue cone bipolar cells in the monkey retina, it is unlikely that the labeled bipolar cells are exclusively blue cone bipolar cells, which are reported to ramify in a single stratum of the inner plexiform layer (34). Thus the presence of two strata of ramification in the inner plexiform layer suggests that other classes of cone bipolar cells express the transgene as well.…”
Section: Discussionmentioning
confidence: 99%
“…Inner S-cone bipolar cells (1S in Fig. 1B) were contacted by multiple, widely spaced S-cone pedicles (Mariani, 1984;Kouyama & Marshak, 1992;Dacey, 1993a). Like diffuse bipolar cells, their main dendrites branched at the INL0 OPL border.…”
Section: Identification Of Retinal Cellsmentioning
confidence: 99%
“…Dacey and colleagues (Dacey and Packer, 2003;Dacey et al, 2005) identified at least two kinds of ganglion cells that carry strong Sϩ signals and at least one type of SϪ cell, but the pathways that provide S-cone signals to these cells are not yet clear. Although it has long been established that a specialized bipolar cell carries Sϩ signals (Mariani, 1984;Kouyama and Marshak, 1992), the existence of an SϪ bipolar cell remains controversial (Klug et al, 2003;. If there is no such cell, Sϩ signals might be inverted and provided to the ganglion cell by amacrine cells or might feed an inverting synapse on the ganglion cell.…”
Section: Structural Basis For Chromatic Properties Of S؉ and S؊ Cellsmentioning
confidence: 99%